One-dimensional boron nitride microribbon as well as preparation method and application thereof
Through a multi-step hydrothermal reaction and nitriding treatment method, a high-purity one-dimensional boron nitride microband was successfully prepared, which solved the problems of limited yield, low purity and structural defects of boron nitride materials in the prior art, achieved efficient and controllable large-scale production, and significantly improved the mechanical and thermal conductivity of the material.
Patent Information
- Application Number
- CN202411888342.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art has problems such as limited yield, low purity and structural defects in the preparation of one-dimensional boron nitride materials, which seriously restricts the application potential of boron nitride materials in many fields.
A preparation method including the following steps is adopted: firstly, zinc sulfate, sodium tetraborate and ammonium borate are mixed and dissolved in deionized water, adjust the pH to 8-11, and perform the first hydrothermal reaction to obtain a first-order boron-containing precursor; then perform the second hydrothermal reaction to obtain a second-order boron-containing precursor; finally, heat up to the calcination temperature under a nitrogen atmosphere to obtain a white boron nitride powder, i.e., a one-dimensional boron nitride microband.
The one-dimensional boron nitride microband prepared by this method has high purity and high raw material conversion rate. It is suitable for mass production and can be used to improve the mechanical properties and thermal conductivity of epoxy resins.
Smart Images

Figure HDA0005199945320000011 
Figure HDA0005199945320000012 
Figure HDA0005199945320000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic materials, and specifically relates to a one-dimensional boron nitride micron belt and a preparation method and application thereof. Technical Background
[0002] Hexagonal boron nitride (h-BN) has excellent comprehensive properties, such as high thermal conductivity, low expansion coefficient, excellent electrical insulation and corrosion resistance, etc., so it is often used in aerospace, metallurgy, cosmetics and other fields. In recent years, the research on boron nitride with different morphologies and sizes has received widespread attention, and a large number of BN materials with excellent properties have been continuously reported, showing the broad application prospects of BN materials in new energy, electronics, machinery and other fields.
[0003] The synthesis process of boron nitride is highly sensitive to reaction conditions, and its products suffer from defects such as limited yield, poor purity and dense defects. These limitations significantly restrict the application potential of boron nitride materials in various fields.
[0004] At present, the main methods for preparing one-dimensional boron nitride materials are ball milling annealing, chemical vapor deposition (CVD), etc. For example, Chen et al. used ball milling annealing to grind crystalline boron with stainless steel balls, and synthesized boron nitride nanotubes with detached metal particles as catalysts, amorphous boron as boron source, and nitrogen or ammonia as nitrogen source, but the product purity was not high, and the tube diameter and length were unevenly distributed. Loμrie et al. used borazine (B3N3H6) as a precursor, and generated boron nitride nanotubes on the surface of nickel boride under the catalysis of nickel boride, but the product was impure and contained boron nitride nanostructures with other morphologies. Tang et al. used melamine and boric acid to dry and calcine, and then introduced ammonia for nitridation to generate boron nitride whiskers. The whisker diameter was 0.1-3μm and the diameter was 15-100μm. The whisker morphology was greatly affected by the heat treatment temperature and the uniformity was poor. Wang et al. used a hydrothermal method to prepare a boron-containing precursor and introduced ammonia gas for nitridation to synthesize boron nitride microbelts. However, the hydrothermal temperature was low when synthesizing the precursor, the precursor had low crystallinity, the nitridation time was too long, the content of ribbon morphology was not high, and the boron nitride microbelts had many defects.
[0005] Therefore, although there have been many methods to try to synthesize one-dimensional boron nitride materials, these methods all have problems such as limited yield, low purity and structural defects, which seriously restrict the application potential of boron nitride materials in many fields. Developing a new method that is efficient, controllable and can mass-produce high-purity one-dimensional boron nitride materials has become a key technical challenge that needs to be solved urgently. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a one-dimensional boron nitride micron belt and a preparation method thereof in view of the above-mentioned deficiencies in the prior art. The product prepared by the method has high purity and high raw material conversion rate, and is very suitable for mass production.
[0007] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0008] A method for preparing a one-dimensional boron nitride microbelt mainly comprises the following steps:
[0009] (1) Mix zinc sulfate, sodium tetraborate and ammonium borate and dissolve them in deionized water, adjust the pH to 8-11 with ammonia water, and stir for a period of time to obtain a mixed solution:
[0010] (2) pouring the mixed solution obtained in step (1) into a sealed reactor and placing it in a forced air drying oven for a first hydrothermal reaction; after the first hydrothermal reaction is completed, naturally cooling to room temperature, filtering, washing, and drying the product in the reactor to obtain a primary boron-containing precursor;
[0011] (3) pouring the first boron-containing precursor obtained in step (2) into a sealed reactor and placing it in a forced air drying oven for a second hydrothermal reaction; after the second hydrothermal reaction is completed, naturally cooling to room temperature, washing and drying the product in the reactor, and obtaining a second boron-containing precursor [B-Zn-O];
[0012] (4) The secondary boron-containing precursor obtained in step (3) is heated to a calcination temperature in a nitrogen-containing atmosphere and kept at this temperature for a period of time to obtain a white boron nitride powder, i.e., a one-dimensional boron nitride microbelt.
[0013] According to the above scheme, in step (1), the molar ratio of zinc sulfate, sodium tetraborate and ammonium borate is 1:(0.2-1.2):(1.6-2.4), and the optimal molar ratio is 1:0.8:2.
[0014] According to the above scheme, in step (1), the pH is adjusted using ammonia water with a concentration of 25% to 28%.
[0015] According to the above scheme, in step (2), the hydrothermal temperature is 100-160°C, and the time is 6-24 hours; the drying temperature is 60-80°C, and the drying time is 6-24 hours.
[0016] According to the above scheme, in step (3), the hydrothermal temperature is 140-240°C and the insulation time is 6-24h.
[0017] According to the above scheme, in step (4), the calcination temperature is 1000-1400°C, and the holding time at the calcination temperature is 0.5-6h; the temperature is increased to the calcination temperature at a heating rate of 3-10°C / min; the nitrogen-containing atmosphere is NH3 atmosphere, and ammonia is continuously introduced at a flow rate of 50-500ml / min to form a nitrogen-containing atmosphere.
[0018] The boron nitride prepared by the above method has a one-dimensional solid ribbon structure, with a length mainly concentrated in the range of 10 to 30 μm, a width mainly concentrated in the range of 1 to 2 μm, an aspect ratio mainly concentrated in the range of 10 to 30, and a thickness not exceeding 0.5 μm.
[0019] On the basis of the above, the present invention also provides a method for preparing an epoxy resin composite material filled with boron nitride micro-belts, which specifically comprises the following steps:
[0020] 1) After degassing the epoxy resin, the boron nitride microbelt prepared by the present invention and the diluent are added, stirred at 40-60° C. for 1-3 hours, and then a curing agent is added, and the mixture is further stirred at 40-60° C. for 20-40 minutes, and then degassing again to obtain a mixed solution;
[0021] 2) pouring the mixed solution obtained in step 1) into a mold (the mold is pre-sprayed with a release agent and dried and preheated to 40-60° C.), curing at 70-90° C. for 3-5 hours, and then heating to 110-130° C. to continue curing for 1-3 hours; after the curing is completed, cooling to room temperature and demolding can obtain the epoxy resin composite material filled with boron nitride micro-belts.
[0022] According to the above scheme, in step 1), the amount of boron nitride microbelt added does not exceed 5% of the mass of the mixed liquid (i.e. the total mass of the epoxy resin, diluent and curing agent); the diluent and curing agent are 20-30% and 30-40% of the mass of the epoxy resin respectively.
[0023] The present invention involves the preparation of precursors and nitridation reactions to prepare boron nitride. The following reactions may occur during the synthesis process:
[0024] Zn 2+ +OH - →Zn(OH)2
[0025] B4O7 2- +OH - +H2O→B(OH)4 -
[0026] Zn(OH)2+4B(OH)4 - →xZnO·yB2O3·zH2O
[0027] xZnO·yB2O3·zH2O+H2O→[B-Zn-O]+H2O
[0028] [B-Zn-O]→ZnO+B2O3
[0029] NH3→N * +H2
[0030] B2O3+N *+H2→BN microribbons(BNMRs)+H2O
[0031] In the present invention, the possible reaction mechanism for preparing one-dimensional boron nitride microbelts is as follows: the first hydrothermal synthesis obtains a primary boron-containing precursor xZnO·yB2O3·zH2O; in the secondary hydrothermal process, the primary boron-containing precursor xZnO·yB2O3·zH2O dissolves and precipitates under high temperature and high pressure conditions and then recrystallizes to form a secondary boron-containing precursor [B-Zn-O]. Subsequently, the secondary boron-containing precursor [B-Zn-O] is placed in a tubular furnace for nitridation. During the nitridation process, as the temperature gradually rises, [B-Zn-O] decomposes into zinc oxide and boron oxide. Under high temperature conditions, boron oxide precipitates from the surface of the precursor, and the internal boron element continuously diffuses to the outside due to its high concentration, and ammonia decomposes active N at high temperature. * , boron oxide and N * The reaction forms one-dimensional boron nitride microribbons.
[0032] In the present invention, the one-dimensional boron nitride microbelt is filled into the epoxy resin, which can significantly improve the mechanical properties and thermal conductivity of the composite material. The high thermal conductivity of the one-dimensional boron nitride microbelt effectively promotes the transfer of heat by forming a thermal conductive network in the composite material, thereby enhancing the overall thermal management capability of the composite material. At the same time, the good interface bonding between the one-dimensional boron nitride microbelt and the epoxy resin matrix can significantly improve the mechanical properties of the composite material.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The one-dimensional boron nitride microbelt provided by the present invention is a solid strip at the micron level. It not only has high product purity and raw material conversion rate, but also low raw material price, simple and efficient preparation process, and successfully solves the key problems of one-dimensional boron nitride materials in terms of purity, raw material cost and production efficiency. It can produce high-purity one-dimensional boron nitride microbelt products on a large scale industrially without the support of high-end equipment, which significantly reduces production costs and improves production efficiency.
[0035] 2. The boron nitride microbelt prepared by the present invention can be used to improve the mechanical properties of epoxy resin, has good strengthening and toughening effects, and can also significantly improve its thermal conductivity, and has extremely high application value and economic potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The following are scanning electron microscope (SEM) images and EDS spectra of the boron nitride obtained in Comparative Example 1.
[0037] Figure 2 The following are scanning electron microscope (SEM) images and EDS spectra of the boron nitride microbelt obtained in Example 1.
[0038] Figure 3 : This is the X-ray diffraction (XRD) pattern of the boron nitride microbelt obtained in Example 1.
[0039] Figure 4 This is a diagram showing the mechanical properties of a boron nitride microbelt epoxy resin composite material prepared by filling the boron nitride microbelt obtained in Example 1 into epoxy resin.
[0040] Figure 5 This is an infrared thermal imaging image of the temperature rise of the boron nitride microbelt epoxy resin composite material prepared by filling the boron nitride microbelt obtained in Example 1 into epoxy resin on a heating plate at 80°C.
[0041] Figure 4 and Figure 5 In the formula, pure EP represents E51 epoxy resin; x wt% BNMRs / EP represents epoxy resin composite material filled with one-dimensional boron nitride microbelts; and x wt% represents the filling amount of one-dimensional boron nitride microbelts, which is between 1 and 4. DETAILED DESCRIPTION
[0042] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with embodiments, but the content of the present invention is not limited to the following embodiments.
[0043] In the following examples and comparative examples, the X-ray diffraction analysis (XRD) of the obtained products was performed using a Rigaku D / MAX-LLIA X-ray powder diffractometer. 2θ is 5-80°; the internal microstructure and energy spectrum analysis are observed using a SΜ8600 Hitachi scanning electron microscope (SEM). The mechanical properties of the boron nitride micro-belt epoxy resin composite material are tested using a DDL200KN universal mechanical testing machine. The infrared thermal imaging image of the boron nitride micro-belt epoxy resin composite material heated on an 80°C heating plate is tested using a TESTO-865 infrared thermal imager.
[0044] Comparative Example 1
[0045] A method for preparing boron nitride comprises the following steps:
[0046] (1) According to the molar ratio of ZnSO4·7H2O, Na2B4O7·10H2O and NH4HB4O7·3H2O being 1:0.8:2, 1.435 g ZnSO4·7H2O, 1.526 g Na2B4O7·10H2O and 2.283 g NH4HB4O7·3H2O were weighed, 80 mL deionized water was added and the mixture was fully mixed and stirred for 30 min, the pH was adjusted to about 9.5 with 25% ammonia water, and then the mixture was placed in a hydrothermal reactor and sealed, and placed in a forced air drying oven at 100° C. for 12 h; after the insulation was completed, the mixture was naturally cooled to room temperature, filtered, washed, and dried in a forced air drying oven at 60° C. for 12 h to obtain a primary boron-containing precursor;
[0047] (2) The first-level boron-containing precursor obtained in step (1) is evenly placed in an alumina crucible, placed in a tubular furnace, and after vacuuming, ammonia is continuously introduced at a flow rate of 200 ml / min, and the temperature is increased to 1150°C at a rate of 5°C / min, and kept warm for 0.5 h; after the insulation is completed, the furnace is cooled to 200°C, the vent valve is closed, and the mixture is naturally cooled to room temperature to obtain a boron nitride sample.
[0048] like Figure 1 As shown, the SEM image of the boron nitride sample prepared in this comparative example shows that most of the boron nitride samples are in granular form, a small amount is in ribbon form, and the content of boron nitride micro-ribbons is relatively low.
[0049] Example 1
[0050] A method for preparing a one-dimensional boron nitride microbelt comprises the following steps:
[0051] (1) According to the molar ratio of ZnSO4·7H2O, Na2B4O7·10H2O and NH4HB4O7·3H2O of 1:0.8:2, 1.435g ZnSO4·7H2O, 1.526g Na2B4O7·10H2O and 2.283g NH4HB4O7·3H2O were weighed, 80mL deionized water was added and the mixture was thoroughly mixed and stirred for 30min, the pH was adjusted to about 9.5 with 25% ammonia water, the mixture was put into a hydrothermal reactor and sealed, and placed in a forced air drying oven for 12h at 100°C; after the insulation was completed, the mixture was naturally cooled to room temperature, filtered, washed, and dried in a forced air drying oven at 60°C for 12h to obtain a primary boron-containing precursor.
[0052] (2) The first boron-containing precursor is placed in a hydrothermal reactor and kept at 160° C. in a forced air drying oven for 12 h, cooled naturally to room temperature, and washed and dried to obtain a second boron-containing precursor.
[0053] (3) The secondary boron-containing precursor prepared above was evenly placed in an alumina crucible, placed in a tubular furnace, and after evacuation, ammonia was introduced at a flow rate of 200 ml / min, and the temperature was raised to 1150°C at a rate of 5°C / min and kept warm for 0.5 h; after the insulation was completed, the furnace was cooled to 200°C, the vent valve was closed, and it was naturally cooled to room temperature to obtain a one-dimensional boron nitride microbelt with an actual yield of 1.3520 g. The theoretical yield of boron nitride was calculated to be 1.5904 g, and the boron nitride yield was about 85%.
[0054] like Figure 2 As shown in FIG. 1 , the SEM image of the boron nitride sample prepared in this embodiment is shown. Figure 2 From the photos, we can see that the boron nitride sample has a one-dimensional strip structure, and about 95% of the field of view is one-dimensional boron nitride micro-ribbons, with the length mainly concentrated in the range of 10 to 30 μm, the width mainly concentrated in the range of 1 to 2 μm, the aspect ratio mainly concentrated in the range of 10 to 30, and the thickness not exceeding 0.5 μm, mainly in the range of 0.1 to 0.5 μm.
[0055] like Figure 3 As shown in the XRD spectrum of the boron nitride microbelt sample prepared in this embodiment, there are three obvious main peaks in the spectrum, which are located at 2θ=26.71°, 42.61°, and 75.95°, respectively. The peaks correspond to the (002), (100), and (110) crystal planes of the h-BN crystal (PDF#34-0421), respectively, without impurity phases, and the purity is very high.
[0056] Example 2
[0057] A method for preparing a one-dimensional boron nitride microbelt comprises the following steps:
[0058] (1) According to the molar ratio of ZnSO4·7H2O, Na2B4O7·10H2O and NH4HB4O7·3H2O of 1:0.2:1.6, 1.435 g ZnSO4·7H2O, 0.381 g Na2B4O7·10H2O and 1.826 g NH4HB4O7·3H2O were weighed, 80 mL deionized water was added and the mixture was thoroughly mixed and stirred for 30 min, the pH was adjusted to about 9.5 with 25% ammonia water, the mixture was placed in a hydrothermal reactor and kept warm at 100°C in a forced air drying oven for 12 h, and a primary boron-containing precursor was obtained after filtration, washing and drying.
[0059] (2) The first boron-containing precursor is placed in a hydrothermal reactor and kept at 160° C. in a forced air drying oven for 12 h, cooled naturally to room temperature, and washed and dried to obtain a second boron-containing precursor.
[0060] (3) The secondary boron-containing precursor prepared above is evenly placed in an alumina crucible, placed in a tubular furnace, and after evacuation, ammonia is introduced at a flow rate of 200 ml / min, and the temperature is raised to 1150°C at a rate of 3°C / min and kept warm for 0.5 h; after the insulation is completed, the furnace is cooled to 200°C, the vent valve is closed, and the crucible is naturally cooled to room temperature to obtain a one-dimensional boron nitride microbelt.
[0061] The theoretical yield of boron nitride was calculated to be 1.0224 g, the actual yield was 0.6937 g, and the boron nitride yield was about 68%.
[0062] The boron nitride microbelts prepared in this embodiment were observed to be boron nitride microbelts in about 60% of the field of view by scanning electron microscopy, and were characterized by XRD patterns, showing no obvious impurity phase.
[0063] Example 3
[0064] A method for preparing a one-dimensional boron nitride microbelt comprises the following steps:
[0065] (1) According to the molar ratio of ZnSO4·7H2O, Na2B4O7·10H2O and NH4HB4O7·3H2O of 1:0.4:1.6, 1.435 g ZnSO4·7H2O, 0.762 g Na2B4O7·10H2O and 1.826 g NH4HB4O7·3H2O were weighed, 80 mL deionized water was added and the mixture was thoroughly mixed and stirred for 30 min, the pH was adjusted to about 9.5 with 25% ammonia water, the mixture was placed in a hydrothermal reactor and kept warm at 100°C in a forced air drying oven for 12 h, and a primary boron-containing precursor was obtained after filtration, washing and drying.
[0066] (2) The first boron-containing precursor is placed in a hydrothermal reactor and kept at 160° C. in a forced air drying oven for 12 h, cooled naturally to room temperature, and washed and dried to obtain a second boron-containing precursor.
[0067] (3) The secondary boron-containing precursor prepared above is evenly placed in an alumina crucible, placed in a tubular furnace, and after evacuation, ammonia is introduced at a flow rate of 200 ml / min, and the temperature is increased to 1150°C at a rate of 3°C / min and kept warm for 2 hours; after the insulation is completed, the furnace is cooled to 200°C, the vent valve is closed, and it is naturally cooled to room temperature to obtain a one-dimensional boron nitride microbelt.
[0068] According to calculation, the theoretical yield of boron nitride is 1.136 g, the actual yield is 0.8376 g, and the boron nitride yield is about 74%.
[0069] The boron nitride microbelts prepared in this embodiment were observed to be boron nitride microbelts in about 65% of the field of view by scanning electron microscopy, and were characterized by XRD patterns, showing no obvious impurity phase.
[0070] Example 4
[0071] A method for preparing a one-dimensional boron nitride microbelt comprises the following steps:
[0072] (1) According to the molar ratio of ZnSO4·7H2O, Na2B4O7·10H2O and NH4HB4O7·3H2O of 1:0.6:2, 1.435 g ZnSO4·7H2O, 1.143 g Na2B4O7·10H2O and 2.283 g NH4HB4O7·3H2O were weighed, 80 mL deionized water was added and the mixture was thoroughly mixed and stirred for 30 min, the pH was adjusted to about 9.5 with 25% ammonia water, the mixture was placed in a hydrothermal reactor and kept warm at 80°C in a forced air drying oven for 12 h, and a primary boron-containing precursor was obtained after filtration, washing and drying.
[0073] (2) The first boron-containing precursor is placed in a hydrothermal reactor and kept at 160° C. in a forced air drying oven for 12 h, cooled naturally to room temperature, and washed and dried to obtain a second boron-containing precursor.
[0074] (3) The secondary boron-containing precursor prepared above is evenly placed in an alumina crucible, placed in a tubular furnace, and after evacuation, ammonia is introduced at a flow rate of 200 ml / min, and the temperature is raised to 1150°C at a rate of 6°C / min and kept at this temperature for 2 h. After the insulation is completed, the crucible is cooled to 200°C with the furnace, the vent valve is closed, and the crucible is naturally cooled to room temperature to obtain a one-dimensional boron nitride microbelt.
[0075] The theoretical yield of boron nitride was calculated to be 1.4768 g, the actual yield was 0.9630 g, and the boron nitride yield was about 65%.
[0076] The boron nitride microbelts prepared in this example were observed to be boron nitride microbelts in about 40% of the field of view by scanning electron microscopy, and were characterized by XRD patterns, showing no obvious impurity phase.
[0077] Example 5
[0078] A method for preparing a one-dimensional boron nitride microbelt comprises the following steps:
[0079] (1) According to the molar ratio of ZnSO4·7H2O, Na2B4O7·10H2O and NH4HB4O7·3H2O of 1:1.2:2, 1.435 g ZnSO4·7H2O, 2.288 g Na2B4O7·10H2O and 2.283 g NH4HB4O7·3H2O were weighed, 80 mL deionized water was added and the mixture was thoroughly mixed and stirred for 30 min, the pH was adjusted to about 9.5 with 25% ammonia water, the mixture was placed in a hydrothermal reactor and kept warm at 80°C in a forced air drying oven for 12 h, and a primary boron-containing precursor was obtained after filtration, washing and drying.
[0080] (2) The first boron-containing precursor is placed in a hydrothermal reactor and kept at 160° C. in a forced air drying oven for 12 h, cooled naturally to room temperature, and washed and dried to obtain a second boron-containing precursor.
[0081] (3) The secondary boron-containing precursor prepared above is evenly placed in an alumina crucible, placed in a tubular furnace, and after evacuation, ammonia is introduced at a flow rate of 200 ml / min, and the temperature is raised to 1150°C at a rate of 6°C / min and kept at this temperature for 6 hours; after the insulation is completed, the crucible is cooled to 200°C, the vent valve is closed, and the crucible is naturally cooled to room temperature to obtain a one-dimensional boron nitride microbelt.
[0082] The theoretical yield of boron nitride was calculated to be 1.8176 g, the actual yield was 0.9832 g, and the boron nitride yield was about 54%.
[0083] The boron nitride microbelts prepared in this embodiment were observed to be boron nitride microbelts in about 50% of the field of view by scanning electron microscopy, and were characterized by XRD patterns, showing no obvious impurity phase.
[0084] Application Examples
[0085] The one-dimensional boron nitride microbelt prepared in Example 1 is used as a filler in epoxy resin to prepare an epoxy resin composite material filled with one-dimensional boron nitride microbelt, which specifically includes the following steps:
[0086] 1) Weigh 5g of E51 epoxy resin and place it in a vacuum drying oven, and vacuum it at 50°C for 20 minutes to completely remove the bubbles in the epoxy resin. Subsequently, add one-dimensional boron nitride microbelts to the epoxy resin (add one-dimensional boron nitride microbelts according to 0%, 1%, 2%, 3%, and 4% of the total mass of the epoxy resin, diluent, and curing agent, respectively, and use this mass percentage as the filling amount of the one-dimensional boron nitride microbelt). Next, add 1.25g of diluent 669, and the resulting mixture is placed in a water bath and stirred at 50°C at 1000 rpm for 2 hours. After that, add 1.75g of curing agent polyetheramine D230, and continue to stir at the same stirring speed in a water bath at 50°C for 30 minutes. Finally, put the evenly stirred mixture back into the vacuum drying oven and vacuum it again at 50°C for 20 minutes to remove new bubbles that may be generated during the mixing process.
[0087] 2) Spray the release agent evenly on the surface of the mold, then place the mold in a drying oven, preheat it at 50°C for 30 minutes, pour the mixed solution prepared in step 1) onto the mold, and ensure that the pouring process is complete and correct. After pouring, immediately transfer the mold to a blast drying oven, first cure it at 80°C for 4 hours, then adjust the temperature to 120°C and continue curing for 2 hours. After curing, let the mold slowly cool to room temperature. Finally, perform the demolding operation to obtain a one-dimensional boron nitride microbelt-filled epoxy resin composite material.
[0088] like Figure 4 As shown, this application example fills one-dimensional boron nitride microbelts into epoxy resin, which can significantly improve its mechanical properties, and the maximum tensile strength is better than the epoxy resin before filling. Preferably, the maximum tensile strength of the epoxy resin composite material filled with 2wt% one-dimensional boron nitride microbelts reaches 62.54MPa, which is 65.32% higher than that of the pure epoxy resin matrix.
[0089] like Figure 5 As shown in the figure, this application example fills one-dimensional boron nitride microbelts into epoxy resin, which can significantly improve its thermal conductivity. As can be seen from the figure, under the same heating time, as the content of one-dimensional boron nitride microbelts gradually increases, the temperature that the composite surface can reach is higher. Therefore, the composite material with one-dimensional boron nitride microbelts added has better thermal conductivity than pure epoxy resin, and the thermal conductivity becomes stronger and stronger as the amount of one-dimensional boron nitride microbelts filled gradually increases.
[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a one-dimensional boron nitride microbelt, characterized in that: The main steps are as follows: (1) zinc sulfate, sodium tetraborate and ammonium borate are mixed and dissolved in solvent water, the pH is adjusted to 8-11 with ammonia water, and stirred evenly to obtain a mixed solution after a period of time; (2) subjecting the mixed solution obtained in step (1) to a first hydrothermal reaction to obtain a primary boron-containing precursor; (3) subjecting the primary boron-containing precursor obtained in step (2) to a second hydrothermal reaction to obtain a secondary boron-containing precursor; (4) calcining the secondary boron-containing precursor obtained in step (3) under an NH3 atmosphere to obtain a white boron nitride powder, i.e., a one-dimensional boron nitride microbelt.
2. The method for preparing a one-dimensional boron nitride microbelt according to claim 1, characterized in that: In step (1), the molar ratio of zinc sulfate, sodium tetraborate and ammonium borate is 1:(0.2-1.2):(1.6-2.4).
3. The method for preparing a one-dimensional boron nitride microbelt according to claim 1, characterized in that: In step (1), the molar ratio of zinc sulfate, sodium tetraborate and ammonium borate is 1:0.8:2; and the pH is adjusted using ammonia water with a concentration of 25% to 28%.
4. The method for preparing a one-dimensional boron nitride microbelt according to claim 1, characterized in that: In step (2), the hydrothermal temperature is 100 to 160° C., and the hydrothermal time is 6 to 24 hours.
5. The method for preparing a one-dimensional boron nitride microbelt according to claim 1, characterized in that: In step (3), the hydrothermal temperature is 140 to 240° C., and the hydrothermal time is 6 to 24 hours.
6. The method for preparing a one-dimensional boron nitride microbelt according to claim 1, characterized in that: In step (4), the calcination temperature is 1000-1400°C, and the holding time at the calcination temperature is 0.5-6h; the temperature is increased to the calcination temperature at a heating rate of 3-10°C / min; NH3 gas is continuously introduced at a flow rate of 50-500ml / min to form an NH3 atmosphere.
7. A one-dimensional boron nitride microbelt prepared by the method of claim 1.
8. Use of the one-dimensional boron nitride microbelt according to claim 7 as a filler in epoxy resin.
9. The use according to claim 8, characterized in that: The application method specifically comprises the following steps: 1) After degassing the epoxy resin, add the one-dimensional boron nitride microbelt and the diluent as claimed in claim 7, stir at 40-60° C. for 1-3 hours, then add the curing agent, continue to stir at 40-60° C. for 20-40 minutes, and then degas again to obtain a mixed solution; 2) pouring the mixed solution obtained in step 1) into a mold, curing at 70-90° C. for 3-5 hours, and then heating to 110-130° C. for further curing for 1-3 hours; after the curing is completed, cooling to room temperature, demolding, and obtaining a one-dimensional boron nitride micro-belt filled epoxy resin composite material.
10. The use according to claim 9, characterized in that: In step 1), the amount of boron nitride microbelt added does not exceed 5% of the mass of the mixed solution; the amount of the diluent and the amount of the curing agent are 20-30% and 30-40% of the mass of the epoxy resin respectively.